Pendidikan Islam di Indonesia dan Mesir: Studi Komparatif dalam Pengembangan Kurikulum dan Metode Pengajaran - Maharani, Khairin; Addini, Eza; Yasri, Heldi; Nasution, Nurjamiah; Ahmad, Aprizal (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to conduct a comparative analysis of curriculum development and teaching methods in Islamic education in Indonesia and Egypt. Both countries have a long tradition in the development of Islamic sciences, but they demonstrate different approaches in accordance with their respective social, cultural, and educational policy contexts. This study uses a literature review method with a descriptive qualitative approach through a review of journals, books, and Islamic education policy documents. The results of the analysis show that the Islamic education system in Indonesia emphasizes the integration of religious and general knowledge in its curriculum, in line with the spirit of religious moderation and the demands of modern society. Meanwhile, Islamic education in Egypt, especially through Al-Azhar University, emphasizes a traditional approach based on tafaqquh fi al-din with a focus on mastery of classical Islamic sciences. In terms of teaching methods, Indonesia is more adaptive to active and technology-based learning models, while Egypt maintains the talaqqi and memorization methods, but has begun to adopt modern pedagogical innovations. Overall, both education systems have their own strengths; Indonesia excels in contextualizing the curriculum, while Egypt sets an example in maintaining the authority and continuity of Islamic scholarship. These findings are expected to contribute to the development of a balanced Islamic education that integrates values and modernity.